Corpus-based technology in creating the methodological foundations of the development of lexicography and lexicogrammar of the Uzbek language (Open Academia: Journal of Scholarly Research, 2024)
Ushbu maqola so‘z va grammatik strukturalarni bir-biriga bog‘liq holda o‘rganilishining nazariy-metodologik asosini korpus lingvistikasida aks ettirilishi hususiga bag‘ishlangan